PENGARUH NET INTEREST MARGIN DAN NON PERFORMING LOAN TERHADAP RETURN ON ASSETS PADA BANK KECIL TAHUN 2019-2020 - Venny Aprilia Simbolon; Richard Friendly Simbolon (Jurnal Ekonomis, 2021)
This study measures the effect of Net Interest Margin and NonPerforming Loans on Return on Assets in small banks in 2019-2020. This research is a quantitative research. The data source is obtained from secondary data, namely the 2019-2020 Financial and Annual Reports for small banks. The population in this study are all small banks in Indonesia. The sample in this study was 25 small banks which were selected using purposive sampling method with certain criteria. The variables of this research are net interest margin and non-performing loan as independent variables and return on assets as dependent variable. Data analysis researchers did using SPSS with the analysis carried out is descriptive statistical test, classical assumption test, multiple linear regression, F test, t test, and coefficient of determination test. The results of this study indicate that the Net Interest Margin and Non-Performing Loan have a significant negative effect on Return on Assets.